2021
DOI: 10.1097/mpg.0000000000003097
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance as a Diagnostic Criterion for Metabolically Healthy Obesity in Children

Abstract: Objectives: In recent years, a subgroup of individuals with obesity has been described as having a lower risk of metabolic and cardiovascular complications. These individuals have what is referred to as metabolically healthy obesity (MHO), which has a favorable metabolic profile and a lower probability of longterm complications. The definition of this subtype in children is not clear. The aim of the present study was to determine whether Homeostasis Model Assessment (HOMA) above a set threshold could be the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Although the hyperinsulinemic-euglycemic clamp is considered the gold standard for the identification of insulin resistance, due to its complexity and invasiveness, the most widespread method for assessing insulin resistance among children is through the calculation of HOMA-IR. Studies have found that children with MHO phenotype had lower HOMA-IR index as compared to children with MUO phenotype ( 13 , 29 , 31 , 37 , 38 ), however we did not observe this trend and our finding agrees with other more recent studies ( 39 , 40 ). A study found that both children with MHO and MUO phenotype had significantly higher HOMA-IR when compared to normal weight peers indicating that a state of insulin resistance was already present ( 40 ).…”
Section: Discussionsupporting
confidence: 80%
“…Although the hyperinsulinemic-euglycemic clamp is considered the gold standard for the identification of insulin resistance, due to its complexity and invasiveness, the most widespread method for assessing insulin resistance among children is through the calculation of HOMA-IR. Studies have found that children with MHO phenotype had lower HOMA-IR index as compared to children with MUO phenotype ( 13 , 29 , 31 , 37 , 38 ), however we did not observe this trend and our finding agrees with other more recent studies ( 39 , 40 ). A study found that both children with MHO and MUO phenotype had significantly higher HOMA-IR when compared to normal weight peers indicating that a state of insulin resistance was already present ( 40 ).…”
Section: Discussionsupporting
confidence: 80%
“…An MHO phenotype during childhood is more likely to be retained during adulthood [ 86 , 87 ]. Furthermore, the conversion of MHO children to MUO is determined by the loss of insulin sensitivity [ 88 , 89 ], thus corroborating the hypothesis that MetS begins with obesity but requires IR to develop [ 90 ]. It is important to note that a physiological and transient IR occurs during pubertal development, and it could accelerate the onset of MetS in a pre-existing state of obesity-dependent IR [ 16 , 35 ].…”
Section: Modifiable Risk Factors Of Mets In Childhood and Adolescencementioning
confidence: 62%
“…Given the increase in childhood obesity and its associated complications in adulthood, early detection is of great importance for early intervention, which is why it is important to use precise diagnostic criteria agreed upon by scientific societies [21][22][23]. This is especially true when the presence of symptoms associated with the metabolic syndrome begin to be present during childhood in a significant number of children with obesity [4].…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…Childhood obesity, defined as an excessive accumulation of energy in the form of fat in the pediatric population, is associated with a wide range of serious health complications and an increased risk of early onset of diseases such as diabetes, dyslipidemia, and cardiovascular disease, among others [1,3,4].…”
Section: Introductionmentioning
confidence: 99%